Gợi ý câu a) (các câu khác làm tương tự vì cùng dạng):
⇔\(\left(x-\dfrac{5x}{x+5}\right)^2+2.x.\dfrac{5x}{x+5}=11\)
⇔\(\left(\dfrac{x^2-5x+5x}{x+5}\right)^2+10.x.\dfrac{x^2}{x+5}=11\)
⇔\(\left(\dfrac{x^2}{x+5}\right)^2+10.x.\dfrac{x^2}{x+5}=11\)
Đặt a=\(\dfrac{x^2}{x+5}\)
⇔a2+10a-11=0
⇔a2+11a-a-11=0
⇔a(a+11)-(a+11)=0
⇔(a+11)(a-1)=0
⇔a+11=0 hay a-1=0
*a+11=0
⇔\(\dfrac{x^2}{x+5}\)+11=0
⇔\(\dfrac{x^2+11x+55}{x+5}\)=0
⇔x2+11x+55=0
⇔Phương trình vô nghiệm (bạn tự c/m)
*a-1=0
⇔\(\dfrac{x^2}{x+5}\)-1=0
⇔\(\dfrac{x^2-x-5}{x+5}\)=0
⇔x2-x-5=0
⇔x=\(\dfrac{1+\sqrt{21}}{2}\)hay x=\(\dfrac{1-\sqrt{21}}{2}\)
Vậy tập nghiệm của pt là S={\(\dfrac{1+\sqrt{21}}{2}\);\(\dfrac{1-\sqrt{21}}{2}\)}